Evolving trends in sinus surgery: What is the impact of balloon sinus dilation?. (8th October 2017) - Svider, Peter F.; Darlin, Spencer; Bobian, Michael; Sekhsaria, Vibhav; Harvey, Richard J.; Gray, Stacey T.; Baredes, Soly; Folbe, Adam J.; Eloy, Jean Anderson
Abstract : Objectives/Hypothesis: Balloon dilation (BD) represents a minimally invasive alternative to endoscopic sinus surgery (ESS). Although BD was introduced in 2006, distinct Current Procedural Terminology (CPT) codes were not available until 2011, making prior analysis of population‐based trends difficult. Our objectives were to evaluate these trends and compare any changes to the use of traditional ESS techniques. Geographic trends also were evaluated. Methods: Medicare Part B national datasets encompassing procedures from 2011 to 2015 were obtained. ESS CPT codes (frontal sinusotomy, maxillary antrostomy with/without tissue removal, sphenoidotomy) and BD codes were searched to determine temporal trends in their use. Additionally, state carriers were individually evaluated for geographic trends. Results: National use of BD increased greater than five‐fold (39, 193 from 7, 496 among Medicare patients), whereas the use of ESS increased by only 5.9%. This increase in BD was observed across all sites, including the sphenoid (7.0x), maxillary (5.1x), and frontal (4.7x) sinuses. In the most recent year for which data was available (2015), a significantly greater portion of sinus procedures in these sites utilized BD in the South (42.1%) compared to the Northeast (30.6%), West (29.5%), and Midwest (25.3%) regions ( P  < 0.0001). Conclusion: The performance of BD has increased markedly in recent years. Because the use of ESS codes remain stable, observed BD trends are unlikely to be due simply to greater familiarity with newer CPT coding. The reasons for the striking increase in BD popularity are speculative and beyond the scope of this analysis, but further study may be needed. Level of Evidence: NA. Laryngoscope, 128:1299–1303, 2018